Globalizing an Indian Borderland Environment: Aijal, Mizoram, 1890–1919. (February 2016) - Jackson, Kyle
The borderlands of India's northeast are often seen as historically isolated, remote and inaccessible. In recent years, there has been a growing awareness that such areas were much more open than hitherto assumed. This article tracks dynamic historical change in the Lushai Hills District, or what is today the state of Mizoram. Taking the upland colonial headquarters of Aijal as its vantage point, the article looks closely at the coerced construction of a network of thoroughfares that underwrote new commercial, ecological and missionary presences in the region, and that allowed both the development and dodging of new regimes of state control and surveillance. A borderland- rather than state-centred approach reveals vibrant trans-regional trails of money and information, trade and technology, migrants and labourers, plants and animals. While colonial agents in the early twentieth century sought to congeal longstanding flows of guns and people, restrictive measures were often met with subterfuge and evasion, producing new opportunities and corridors for movement. Understanding Aijal's position as an entrepôtof pluricultural exchange and as an intensifier of regional circulation draws attention to ranges of human experience that stretch beyond the usual state-focussed boundaries of historical inquiry. This article seeks to contribute to a growing literature that challenges the idea of northeast India's remoteness.